The iInvestment modes and its Shariah compliance of Shahjalal Islami Bank Limited - Tia, Tahsin Tasnim (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.